Queer as F**k: Reaching and Engaging Gay Men in Sexual Health Promotion through Social Networking Sites - Pedrana, Alisa; Hellard, Margaret; Gold, Judy; Ata, Nadine; Chang, Shanton; Howard, Steve; Asselin, Jason; Ilic, Olivia; Batrouney, Colin; Stoove, Mark (JMIR Publications, 2013)
BackgroundA growing number of health promotion interventions are taking advantage of the popularity and interactivity of new social media platforms to foster and engage communities for health promotion. However, few health promotion interventions using social networking sites (SNS) have been rigorously evaluated. "Queer as F**k"(QAF) began as pilot project in 2010 to deliver sexual health promotion via short "webisodes" on SNS to gay men. Now in its fifth season, QAF is among the few published examples internationally to demonstrate the sexual health promotion potential of SNS. ObjectiveThe objective of this evaluation is to assess reach, interactivity, and engagement generated by QAF to inform future health interventions and evaluations using SNS. MethodsWe undertook a mixed method process evaluation using an uncontrolled longitudinal study design that compared multiple measurements over time to assess changes in reach and engagement. We adapted evaluation methods from the health promotion, information systems, and creative spheres. We incorporated online usage statistics, interviews informed by user diary-scrapbooks, and user focus groups to assess intervention reach and engagement. ResultsDuring Series 1-3 (April 2010 to April 2011), 32 webisodes were posted on the QAF Facebook and YouTube pages. These webisodes attracted over 30,000 views; ranging from 124-3092 views per individual episode. By April 2011, the QAF Facebook page had 2929 predominantly male fans. Interview and focus group participants supported the balance of education and entertainment. They endorsed the narrative "soap opera" format as an effective way to deliver sexual health messages in an engaging, informative, and accessible manner that encouraged online peer discussion of sexual health and promoted community engagement. ConclusionsQAF offers a successful example of exploiting the reach, interactivity, and engagement potential of SNS; findings from this process evaluation provide a model to inform the delivery and evaluation of future health promotion interventions on SNS.